1999
DOI: 10.1359/jbmr.1999.14.10.1654
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin K Knockout Mice Develop Osteopetrosis Due to a Deficit in Matrix Degradation but Not Demineralization

Abstract: Cathepsin K is a cysteine protease expressed predominantly in osteoclasts. Activated cathepsin K cleaves key bone matrix proteins and is believed to play an important role in degrading the organic phase of bone during bone resorption. Mutations in the human cathepsin K gene have been demonstrated to be associated with a rare skeletal dysplasia, pycnodysostosis. The degree of functional activity of the mutated forms of cathepsin K in these individuals has not been elucidated, but is predicted to be low or absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
300
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(318 citation statements)
references
References 40 publications
14
300
0
4
Order By: Relevance
“…In fact, in vitro and in vivo studies suggest that the 2 types of proteases, MMP-9 and cathepsin K, are involved in bone resorption mediated by osteoclasts, performing the collagen degradation in bone (Delaisse et al, 2003;Everts et al, 1992). Votta et al (1997) found reduced bone resorption, both in vitro and in vivo, using an inhibitor of cathepsin K. Moreover, cathepsin K-deficient mice showed significant osteopetrosis (Saftig et al, 1998;Gowen et al, 1999). In periodontal area, increased levels of cathepsin K Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in vitro and in vivo studies suggest that the 2 types of proteases, MMP-9 and cathepsin K, are involved in bone resorption mediated by osteoclasts, performing the collagen degradation in bone (Delaisse et al, 2003;Everts et al, 1992). Votta et al (1997) found reduced bone resorption, both in vitro and in vivo, using an inhibitor of cathepsin K. Moreover, cathepsin K-deficient mice showed significant osteopetrosis (Saftig et al, 1998;Gowen et al, 1999). In periodontal area, increased levels of cathepsin K Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…42 In conjunction, by inhibition of osteoclastic acidification in vivo by bafilomycin in new bone implants in a rat model, a massive increase in new bone formation was observed. 43 The cathepsin K-deficient patients (pycnodysostosis) and the cathepsin K-null mutation mice that develop osteopetrosis because of a deficit in matrix degradation, but not demineralization 14,16,44 do not display increased levels of osteoclasts. This further indicates that factors released during dissolution of the inorganic phase of the bone are playing a role in osteoclast life span.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Degradation of the organic phase of bone is for the major part mediated by the enzyme cathepsin K, which degrades collagen type I. [12][13][14][15][16] Interestingly, abrogation of degradation of the organic phase of bone does not prevent dissolution of the inorganic phase, because the lowering of …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cathepsin K knockout mice develop osteopetrosis due to a deficit matrix degradation but not demineralization [26]. Similarly, mutations in the human cathepsin K gene have demonstrated an association with a rare skeletal dysplasia, pycnodysostosis [27,28].…”
Section: Osteoclast Physiologymentioning
confidence: 99%